Upgrade of laser pump time‐resolved X‐ray probes in Beijing synchrotron. (22nd October 2019) - Yu, Can; Zhang, Yan; Lei, Ge; Wang, Hao; Wang, Yu-hang; Zhang, Bing-Bing; Sun, Da-Rui; Zhao, Jia-Li; Zhou, Yang-Fan; Li, Qiu-Ju; Gao, Zhen-hua; Zhan, Fei; et al.
Abstract : Adequate time‐resolved X‐ray absorption spectroscopy (TR‐XAS) signal in a 0.3 m M solution was acquired after laser pump/X‐ray probe upgrades. Implementation of simultaneous measurement of both time‐resolved X‐ray diffraction (TR‐XRD) and TR‐XAS in a SrCoO2.5 thin film was carried out. Abstract : The upgrade of the laser pump time‐resolved X‐ray probes, namely time‐resolved X‐ray absorption spectroscopy (TR‐XAS) and X‐ray diffraction (TR‐XRD), implemented at the Beijing Synchrotron Radiation Facility, is described. The improvements include a superbunch fill, a high‐efficiency fluorescence collection, an efficient spatial overlap protocol and a new data‐acquisition scheme. After upgrade, the adequate TR‐XAS signal is now obtained in a 0.3 m M solution, compared with a 6 m M solution in our previous report. Furthermore, to extend application in photophysics, the TR‐XAS probe is applied on SrCoO2.5 thin film. And for the first time, TR‐XAS is combined with TR‐XRD to simultaneously detect the kinetic trace of structural changes in thin film.